Wat maakt het verschil? Levensbeschouwelijke diversiteit in zorginstellingen - Martin Walton (Religie & Samenleving)
In health care institutions, religious and worldview diversity is dealt with in the context of three practices: multicultural care programs, moral deliberation and spiritual (or chaplaincy) care. Whereas in the first two diversity seems to be constituent of the practices, universalizing tendencies in chaplaincy care have limited the appreciation of difference and the development of the handwork of interfaith chaplaincy. In an empirical study by Cadge and Sigalow only two strategies are noted: neutralizing and code-switching. Both strategies, however, tend to neglect the significance of religious and cultural difference. A comparison with pastoral approaches to cultural difference formulated by Lartey leads to the formulation of criteria for strategies of interreligious and intercultural care along with the suggestion of several more strategies.